Nurse’s educational function in reference to patients in surgical ward - Girzelska, Joanna; Kościołek, Aneta; Mianowana, Violetta; Cuber, Tomasz; Wąsik, Andrzej (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Educational activities performed by a nurse during ongoing changes in health care service concerning economic conditions should be calculated as one of the most effective area for medical institutions. Proper education directed to a patient causes the increase of satisfaction with a little financial contribution. On the other hand satisfaction of a patient influences the assessment of the quality of medical service realised by a particular institution of health sector. Education of a patient is the process of the followed in succession and logically connected activities which are performed to change patient’s behaviour. The range of changes should be defined in the course of formulating the aim of education, which significantly influences attitudes, beliefs and motives of a patient. So, the aim of health education of a patient at the surgical ward is to acquaint patient with knowledge and skills concerning: self-control and self-caring what is the essential factor for disease development, its consequences and restoring to health. The aim of the study. Considering the complexity of problems at surgical ward and health consulting the aim of the study was to show to what degree the educational function of a nurse is performed in reference to patients from surgical ward. Material and methods. The research was conducted in 2005 at the Ward of General Surgery and Traumatology in the Public Hospital in Kraśnik. The research material was collected by the method of diagnostic survey with a use of the three self-constructed questionnaires. 200 patients and 60 nurses took part in the study. The collected data were statistically and descriptively analysed. Results and conclusions. The results have allowed to recognise problems that a nurse should consider when planning the educational activities, individual and group ones, both. The analysis of material shows that knowledge of the surgical ward patients about healthy behaviour stays at the basic level. There is no significant relation noticed among the respondents’ opinions between healthy behaviour of patients and existed diseases. The majority of patients do not connect their present lifestyles with the disease they have. More than 80% of them pointed out that information given by nursing personnel were sufficient for them. On the other hand, nurses assess their educational activities as something needful and causing notable prophylactic and preventive effect. Summing up it might be emphasized that educational function of surgical nurses is performed at the satisfactory level. Nursing Topics 2010; 18 (4): 420-428